Sistem Informasi Geografis Pelanggan Berbasis Web PDAM Tirta Kepri Tanjungpinang - Jajang Nurjaman; Dedi Djunaedi (LPPM Universitas Putera Batam, 2022)
The digital era as it is currently requires every organization and individual to follow the pace of technological development, not least PDAM Tirta Kepri which is required to further improve service to the community both administratively and technically, Based on the results of observations and interviews with the service department at PDAM Tirta Kepri Tanjungpinang is an administration activity at the time of registering new installations for customers and the slow pace of data collection. customer location if there is a problem of complaints or arrears. In addition, officers have difficulty checking the available network when there are new customers who sign up. Based on existing problems, the author analyzed and made the design of a geographical information system in order to make it easier administratively for new customers to register for network installation and create facilities for users when going to file complaints and can also make it easier for officers to find customer locations, in this study also carried out the design of pipeline maps to help officers when checking based pipelines. Website, the methodology used for software development using waterfall methods and for system development using DFD while the language used for system development uses PHP programming language to create maps used opensource libraries i.e. leaflets. With the construction of the system can increase time efficiency and effectiveness and can increase productivity in carrying out work, especially in improving service to customers.